Autour d'un double-sens d'anus: une affaire scabreuse ou un jeu littéraire? Enquête sur Pétrone, Sat. 138 - Chappuis Sandoz, Laure (My University, 2006)
This paper offers a new reading of the salacious episode of therapeutic sodomy performed by Oenothea in Petronius' Satiricon (138). Is this scene only pornography? A closer examination shows that Petronius deliberately uses puns and plays with literary and scenic references. In this very short narrative, the word anus occurs twice, once with its rare anatomical meaning, and once with the more common comic sense of 'old woman'. Another pun lies in the use of fenzine, underlining the per-version of sexual roles: the woman plays a dominant role, empowered by the phallic attribute. This female predominance and the use of a leather dildo have literary precedents in Herodas' Mimiambs 6 and 7, where women used this artefact for their own sexual satisfaction. Greek and Roman iconography also provides abundant parallels. The final discussion is illuminated by the murder of the priapic goose in Sat. 136: dildo and goose are both used for sexual pleasure. Once again, the Greek mime and iconographic representations of phallic birds, especially in Apulian vase-painting, offer telling parallels. In conclusion, Petronius' narrative is essentially a literary play and a verbal masquerade, aiming to provoke the reader's laughter.